ANALISIS DISIPLIN KERJA, MOTIVASI, DAN LOYALITAS TERHADAP KINERJA KARYAWAN PADA KANTOR PERTANAHAN KABUPATEN KEDIRI - Fitriana, Desi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The background of this research is that agency employee performance appraisal needs to be carried out in order to know how an agency's ability to improve employee performance. This performance assessment needs to be done to determine the development of employee performance. In order for agencies to achieve the expected performance, an organization should consider the factors influencing employee performance. The aim of this research is to ascertain the impact of work discipline, motivation, and loyalty on employee performance, whether individually or collectively, at the Kediri Regency Land Office. This study uses a causality quantitative approach. The research sample encompassed the entire staff of the Kediri District Land Office and was subjected to analysis through multiple linear regression using SPSS for Windows version 23 software. The findings of this study indicated that (1) collectively, work discipline, motivation, and loyalty exert a positive and noteworthy impact on employee performance within the Kediri District Land Office. (2) Individually, work discipline, motivation, and loyalty hold a positive and significant influence on employee performance at the Kediri Regency Land Office.